2007
DOI: 10.1016/j.virol.2007.07.025
|View full text |Cite
|
Sign up to set email alerts
|

Expression of p53 and its homolog, p73, in HPV DNA positive oesophageal squamous cell carcinomas

Abstract: Several studies have detected human papilloma virus (HPV) DNA in squamous cell carcinoma of the oesophagus (OSCC). In this study, we analysed OSCC specimens from 114 patients for the presence of HPV DNA, and p53 and p73 expression. HPV DNA was detected in 44.7% of cases, with the low risk HPV11 occurring most frequently. p53 and p73 expression was detected in 70% and 61.4% of cases, respectively. There was no correlation between expression of p53, p73 or HPV infection and tumour grade, or between p53 expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 46 publications
1
21
0
Order By: Relevance
“…Some of the low risk areas include North America, along with countries in Western Asia and Northern and Southern Europe, where the incidence rates range from 1.5 to 6.0 of 100,000. High-risk areas include South Africa, China, Iran, and countries in Eastern Africa, where the incidence rates range from 10 to 25 of 100,000 (35,36). In addition to the known risk factors such as alcohol and tobacco, gastroesophageal reflux disease, nutritional deficiencies, numerous studies have detected HPV) DNA in esophageal cancer specimens, implicating HPV infection as a further risk factor in the development of esophageal cancer (37,38).…”
Section: Discussionmentioning
confidence: 99%
“…Some of the low risk areas include North America, along with countries in Western Asia and Northern and Southern Europe, where the incidence rates range from 1.5 to 6.0 of 100,000. High-risk areas include South Africa, China, Iran, and countries in Eastern Africa, where the incidence rates range from 10 to 25 of 100,000 (35,36). In addition to the known risk factors such as alcohol and tobacco, gastroesophageal reflux disease, nutritional deficiencies, numerous studies have detected HPV) DNA in esophageal cancer specimens, implicating HPV infection as a further risk factor in the development of esophageal cancer (37,38).…”
Section: Discussionmentioning
confidence: 99%
“…Out of the HPV-positive tumours, 50% contained the low-risk HPV-6 DNA and 8% showed HPV-16 DNA. Another study showed that HPV-11 is the predominant type (48%) present in HPV-positive OSCC patients (Matsha et al 2007) in the Transkei region of South Africa. Therefore, the role of low-risk HPV types in tumour development is not very clear.…”
Section: Introductionmentioning
confidence: 99%
“…E6AP is a host ubiquitin ligase and it is required by E6 to exert its cellular effects. Since it has been shown that expression of HPV E6 alone can lead to transformation of host cell, we have focussed our studies with E6 only [16,25,39]. However, the role of E6 proteins in oesophageal cancer is not very clear since the lowrisk HPV11 is the predominant type present in the oesophageal cancer specimens in South Africa [47].…”
Section: Introductionmentioning
confidence: 99%